2023
DOI: 10.3390/nu15143126
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential Benefits of Natural Calcium-Rich Mineral Waters for Health and Wellness: A Systematic Review

Manuela Simona Pop,
Dragoș Cornel Cheregi,
Gelu Onose
et al.

Abstract: This systematic review investigates the potential health and wellness benefits of natural calcium-rich mineral waters. It emphasizes the importance of dietary calcium sourced from natural mineral waters in promoting bone health, maintaining cardiovascular function, aiding in weight management, and enhancing overall well-being. The review process involved the comprehensive analysis of peer-reviewed articles, clinical trials, and experimental studies published within the last decade. Findings reveal that consumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…Some studies believe that compounds such as sulphate, bicarbonate, calcium, and magnesium present in mineral water have health benefits like improving digestion [89][90][91][92][93] mainly due to the direct action of mineral waters on the intestinal epithelium, generating an accelerated process of epithelial renewal, without epithelial disruption [94]. Other benefits of mineral water consumption include improved gastric emptying [95], gastroduodenal peristalsis [96], dyspepsia [97], the activity of the bile ducts [98,99], cholagogue activity [100], increased mineralization [101,102], and a reduction in bone resorption [103]. Studies on mineral water consumption show that frequent intake of mineral water can have health effects on biomarkers of cardiometabolic risk, especially reducing total cholesterol, fasting glucose, and LDL cholesterol [104,105], and the formation of kidney stones [106].…”
Section: Mineral-medicinal Groundwatermentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies believe that compounds such as sulphate, bicarbonate, calcium, and magnesium present in mineral water have health benefits like improving digestion [89][90][91][92][93] mainly due to the direct action of mineral waters on the intestinal epithelium, generating an accelerated process of epithelial renewal, without epithelial disruption [94]. Other benefits of mineral water consumption include improved gastric emptying [95], gastroduodenal peristalsis [96], dyspepsia [97], the activity of the bile ducts [98,99], cholagogue activity [100], increased mineralization [101,102], and a reduction in bone resorption [103]. Studies on mineral water consumption show that frequent intake of mineral water can have health effects on biomarkers of cardiometabolic risk, especially reducing total cholesterol, fasting glucose, and LDL cholesterol [104,105], and the formation of kidney stones [106].…”
Section: Mineral-medicinal Groundwatermentioning
confidence: 99%
“…There are many sources of mineral waters worldwide, and due to their mineralmedicinal properties, several countries market these waters. Europe is a continent abundant in natural mineral waters [109], and there, some countries such as Spain, Slovakia, Romania, Germany, and France bottle and market them for consumption [102,110]. In Italy, these waters are mainly used for recreational purposes [111].…”
Section: Mineral-medicinal Groundwatermentioning
confidence: 99%
See 2 more Smart Citations
“…Human intervention studies showed that drinking low-mineral water exacerbates lipid profile and raises homocystine (an independent cardiovascular disease biomarker) levels [16]. On the contrary, drinking natural mineral water may promote bone health, maintain cardiovascular function, improve lipid profile, aid weight management, and enhance overall well-being [17]. Animal studies also proved that the consumption of low mineral water leads to a higher risk of cardiovascular disease [16] and impaired bone quality [18].…”
Section: Introductionmentioning
confidence: 99%